2022
DOI: 10.1590/fst.58221
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of partial glycerides rich in α-linolenic acid efficiently from silkworm pupa oil with immobilized lipase MAS1-H108A

Abstract: In this paper the ability of immobilized lipase MAS1-H108A to prepare α-linolenic acid-rich partial glycerides was studied. The effects of different reaction conditions on the yield of Diacylglycerol (DAG) and Monoglyceride (MAG) were investigated, including substrate molar ratio, substrate concentration, temperature and lipase dosage. The highest yield (63.92% of MAG and 30.61% of DAG) was obtained when silkworm pupa oil/glycerol ratio of 1:3, lipase dosage was 50 U/g, substrate concentration was 40% (w/v), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, a lipase percentage above 10% did not significantly increase the reaction rate. This phenomenon may be attributed to a saturation interplay between the lipase loading and the substrates or, alternatively, excessive immobilized lipase loading potentially impeding the mass transfer (Yue et al, 2022). Taking into account both the rate of β-sitosterol esterification and the cost implications associated with enzyme usage, an enzyme loading of 150 U was identified as the optimal setting for the process.…”
Section: Effect Of Lipase Loading On the Degree Of Esterificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lipase percentage above 10% did not significantly increase the reaction rate. This phenomenon may be attributed to a saturation interplay between the lipase loading and the substrates or, alternatively, excessive immobilized lipase loading potentially impeding the mass transfer (Yue et al, 2022). Taking into account both the rate of β-sitosterol esterification and the cost implications associated with enzyme usage, an enzyme loading of 150 U was identified as the optimal setting for the process.…”
Section: Effect Of Lipase Loading On the Degree Of Esterificationmentioning
confidence: 99%
“…The crystal structure of this enzyme reveals the presence of disulfide bonds and salt bridges, which contributes to its remarkable thermostability (Yuan et al, 2016; Zhao et al, 2022). Our following studies have shown that lipase UM1 is highly valuable in various industrial applications, such as the production of n‐3 polyunsaturated fatty acids (PUFA)‐rich triacylglycerols (TAG) (Wang et al, 2016), n‐3 polyunsaturated fatty acids (PUFA)‐rich lysophosphatidylcholine (LPC) (Wang et al, 2020), biodiesel (Wang et al, 2017), and partial glycerides enriched with α‐linolenic acid (Lian et al, 2018; Yue et al, 2022). Specifically, the contents of n‐3 PUFA‐rich TAG synthesized by lipase UM1 reached 92.07% and 76.13% during the esterification and glycerolysis reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the defects of natural extraction and chemical synthesis, we need to find a new method to produce natural flavor compounds. The catalytic synthesis of enzyme has the advantages of mild reaction conditions, high catalytic efficiency and strong catalytic specificity,which is a typical green and environmentfriendly process for the synthesis of perfume (Yue et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…and remain in the environment for a long time. Some carboxylic acids are difficult to dissolve or extremely unstable in organic solvents, whereas esters can dissolve and remain stable in almost all organic solvents (Yue et al, 2022). Therefore, transesterification of esters is more important than direct esterification of alcohol and acid, which makes enzyme catalyzed transesterification reactions to synthesize perfume ester an important research direction (Shah et al, 2004;Gómez et al, 2020;Febriani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%